Assessing public support for restrictions on transport of invasive wild pigs (Sus scrofa) in the United States. (1st May 2019) - Grady, Meredith J.; Harper, Erin E.; Carlisle, Keith M.; Ernst, Karina H.; Shwiff, Stephanie A.
Abstract: Wild pigs ( Sus scrofa ) are a non-native invasive species in the United States that cause significant economic loss, transmit disease, and inflict damage upon natural resources, agriculture, livestock, and property. Geographic distribution of wild pigs in the United States has nearly tripled since 1982, with anthropogenic influences playing a significant role in the expansion. In this regard, there is speculation that a driver of the expansion may be human-mediated movement of wild pigs to new areas for the purpose of sport hunting. In response, states have implemented a variety of wild pig control policies, including legal restrictions on their transport. The success of such policies depends, in part, on their level of public support, which in turn may be influenced by individuals' attitudes concerning wild pigs, their interest in maintaining wild pig populations (e.g., for sport hunting), and their knowledge and awareness of the threats wild pigs pose. Multiple regression was used to analyze data collected from a nationwide survey concerning attitudes toward wild pigs and policies that restrict their transport. Results indicate that a majority of individuals in the United States have negative attitudes toward wild pigs and support policies that restrict their transport and penalize transgressors. Consistent with other invasive species research, findings suggest that as knowledge and awareness of wild pigs increase, so too does support for policies restricting and penalizing transport of wild pigs. Contrary to previous studies, this research also finds that hunters are more likely to support restrictions on wild pig transport than are non-hunters. Overall, these findings suggest that legal restrictions on the transport of wild pigs, even in states with large hunter populations, enjoy broad public support and may help to curb the expansion of wild pig populations. Highlights: We conducted a nationwide survey to understand attitudes toward wild pig transport. A majority of the U.S. public holds negative attitudes toward wild pigs. As knowledge and awareness increase, support for transport restrictions increases. A majority of the U.S. public support legal restrictions for transporting wild pigs. Hunters have greater support for restrictions and penalties than the general public.